2018
DOI: 10.22325/fes/res.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Comportamientos ambientales en Europa. Una mirada desde el consumo colaborativo

Abstract: Las contradicciones entre declaraciones de valores y comportamientos son frecuentes cuando se aborda el tema medioambiental. Esta investigación profundiza en las prácticas pro-ambientales a nivel europeo. Para explicar las prácticas pro-ambientales se incluyen factores que van más allá de la conciencia ecológica, partiendo de la lógica de que los comportamientos pro-ambientales no tienen por qué provenir únicamente de una postura ecocéntrica. Además de observar los condicionantes externos se explora la posible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Suárez Vergne (2018) [53] found that there are differences at the European level in environmental practices. Specifically, approaches vary between the block of Liberal, Continental and Nordic States and the block of Mediterranean and Eastern States.…”
Section: European Regionmentioning
confidence: 99%
“…Suárez Vergne (2018) [53] found that there are differences at the European level in environmental practices. Specifically, approaches vary between the block of Liberal, Continental and Nordic States and the block of Mediterranean and Eastern States.…”
Section: European Regionmentioning
confidence: 99%